2011
DOI: 10.1007/s00382-011-1049-6
|View full text |Cite
|
Sign up to set email alerts
|

Regional climate simulations over South America: sensitivity to model physics and to the treatment of lateral boundary conditions using the MM5 model

Abstract: In this study the capability of the MM5 model in simulating the main mode of intraseasonal variability during the warm season over South America is evaluated through a series of sensitivity experiments. Several 3-month simulations nested into ERA40 reanalysis were carried out using different cumulus schemes and planetary boundary layer schemes in an attempt to define the optimal combination of physical parameterizations for simulating alternating wet and dry conditions over La Plata Basin (LPB) and the South A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 55 publications
1
26
0
Order By: Relevance
“…However, it is important to note that the maximum precipitation associated with the SACZ is underestimated by around 3 mm/day. The systematic underestimation of precipitation in tropical areas with the Grell scheme has also been documented by Solman and Pessacg (2012a) with the MM5 regional model, by Fernán-dez et al (2006) and da Rocha et al (2009) with the RegCM3 regional model, and by Chou et al (2012) with the Eta regional model. While the MM5 model captures the observed maximum of precipitation in areas of high topography, its magnitude is overestimated.…”
Section: Validation Of Surface Variables For Presentsupporting
confidence: 55%
See 1 more Smart Citation
“…However, it is important to note that the maximum precipitation associated with the SACZ is underestimated by around 3 mm/day. The systematic underestimation of precipitation in tropical areas with the Grell scheme has also been documented by Solman and Pessacg (2012a) with the MM5 regional model, by Fernán-dez et al (2006) and da Rocha et al (2009) with the RegCM3 regional model, and by Chou et al (2012) with the Eta regional model. While the MM5 model captures the observed maximum of precipitation in areas of high topography, its magnitude is overestimated.…”
Section: Validation Of Surface Variables For Presentsupporting
confidence: 55%
“…Moreover, it has been shown that IV is sensitive to the simulated period, the domain size and geographic location. This has motivated several studies focused on evaluating IV, such as those that aim for assess the magnitude of IV in RCMs and characterize both spatial and temporal distribution, as well as its dependence on the number of ensemble members and the domain size (Giorgi and Bi, 2000;Christensen et al, 2001 over the Mediterranean region, southern Europe and northern Africa; Caya and Biner, 2004;Alexandru et al, 2007;Lucas-Picher et al, 2008 in North America; Vanvyve et al, 2008 for western Africa;and Solman and Pessacg, 2012a for South America). Moreover, the IV represents the lowest level of uncertainty that cannot be reduced, but should be characterized in order to assess the extent to which the response of the regional climate represents a significant signal or is immersed in the inherent uncertainty of the RCM.…”
Section: Introductionmentioning
confidence: 99%
“…The WRF3.1.1 used the KF cumulus scheme and the YSU PBL scheme, which have been tested over the region with good results by Tadross et al (2005) using MM5 andCr etat et al (2012) using WRF3.1.1. Solman and Pessacg (2012) show the KF scheme to be most suitable in subtropical regions, so it is unclear to the authors why WRF3.1.1 should introduce such a wet bias to the region. With the exception of WRF3.1.1, the models produce a dry bias over the northeast of the domain more specifically over Mozambique and the south part of Malawi (Nikulin et al 2012;Kim et al 2013), which is more likely related to circulation anomalies that shift the south Indian convergence zone west (Cook 2000) than directly to the cumulus parameterization.…”
Section: B Model Biasesmentioning
confidence: 99%
“…Tchotchou and Kamga (2010) caution in their study of the West African monsoon using RegCM3 that unrealistic soil moisture resulting from the way albedo has been parameterized was a leading cause of an excessive northward penetration of monsoon flow. Solman and Pessacg (2012) attributed the underestimation of precipitation over the La Plata Basin by the MM5 to be largely due to a misrepresentation of the moisture flux convergence. New et al (2003), Steiner et al (2009), Wu et al (2009, Alo and Wang (2010), Xue et al (2010), and Ruti et al (2011) draw attention to the importance of the land surface scheme in simulating the West African monsoon.…”
Section: B Model Biasesmentioning
confidence: 99%
“…(Grell et al 1994). Solman and Pessacg (2011) summarizes the overall model performance over SA. All the simulations in this study were performed using the explicit moisture scheme by Hsie et al (1984).…”
Section: Itczmentioning
confidence: 99%